Freedom of Information - A Literature Review - Treadwell, G (Journalism Education Association of New Zealand (JEANZ), 2015)
When Mexican president Enrique Peña Nieto launched the third summit of the Open Government Partnership (OGP) in October, 2015, outside the event protesters disputed the highly scripted account of his government’s transparency. Worldwide, the membership of the OGP may be growing but increasingly scholars and journalists are reporting a degradation of freedom of information (FOI), even in so-called liberal societies like Aotearoa-New Zealand. Stemming from a doctoral review of FOI scholarship, this paper traces the literature from early scholarship on FOI’s role in democratic governance to a contemporary focus on emergent ‘push’ systems advocated for by the OGP. Scholars increasingly situate access to state-held information as a fundamental human right but also describe scepticism among journalism practitioners and researchers alike about the realpolitik success of FOI regimes. Among other things, including a growing structural pluralism that has cast information shadows over state expenditure, scholars have recorded governmental tendencies to return to state secrecy since the declaration by the West of the so-called war on terror.This paper also considers literature on Aotearoa-New Zealand’s FOI regime and argues that the scholarship has largely beenproduced by legal-studies and policy-studies scholars, to the detriment of a complete picture of FOI. It outlines what research does exist within journalism studies but contends that a lack of more significant contributions has restricted our understanding of the regime. It outlines a need for further scholarship on FOI on Aotearoa-New Zealand in light of both global and local trends.